The influence of prenatal nutrition on ruminal microbiome of beef cattle - Furlan, Édison; Polizel, Guilherme Henrique Gebim; Fernandes, Arícia Christofaro; Prati, Bárbara Carolina Teixeira; Pombo, Gabriela do Vale; Ramírez-Zamudio, Germán Darío; Fukumasu, Heidge; Santana, Miguel Henrique de Almeida (Frontiers in Genetics, 2026)
IntroductionMaternal nutrition is recognized for inducing long-lasting effects on offspring performance during postnatal life. However, little is known about its potential role in modulating the ruminal microbiota during fetal development, as rumen colonization has traditionally been assumed to occur only at birth. This study aimed to evaluate the long-term effects of maternal nutrition during gestation on the offspring’s ruminal microbiota in postnatal life.MethodsThe experimental design comprised 28 Nellore bulls, offspring of a single sire and born to primiparous heifers. Dams were assigned to two groups and received either mineral supplementation (Control; n = 14; 0.3 g/kg BW) or protein–energy supplementation (Supplemented; n = 14; 5 g/kg BW) throughout gestation, from conception to calving. Calves from both groups were managed identically from birth to slaughter. At the finishing phase, ruminal fluid samples were collected from 10 bulls per treatment. The V4 region of the 16S rRNA gene was sequenced, and amplicon sequence variants (ASVs) were identified using DADA2 and phyloseq for microbial diversity and taxonomic analysis. Pathway over-representation analysis was also conducted using MicrobiomeProfiler.Results and DiscussionMaternal nutrition resulted in modest yet significant alterations in the ruminal microbial communities of the offspring. The Supplemented group exhibited higher relative abundance of Fibrobacter and Prevotellaceae UCG-003, with reduced abundance of Xylanibacter. Pathway analysis revealed enrichment of starch and sucrose metabolism, along with modulation of amino acid biosynthesis and nitrogen metabolism, suggesting potential improvements in microbial protein synthesis and nitrogen utilization. In conclusion, maternal nutrition during gestation has long-term effects on the offspring’s ruminal microbiota, influencing specific bacterial taxa and metabolic pathways linked to carbohydrate metabolism and nutrient utilization.